(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
The pharmaceutical industry plays a vital role in improving global health, but it also generates significant environmental challenges through the extensive use of hazardous chemicals, large solvent consumption, high energy demand, and waste production. Green Chemistry and Green Analytical Chemistry (GAC) have emerged as complementary approaches that promote sustainability across the entire pharmaceutical lifecycle, from drug synthesis to quality control. Green Chemistry focuses on designing environmentally friendly manufacturing processes by reducing toxic reagents, employing renewable feedstocks, utilizing safer solvents, improving energy efficiency, and minimizing waste through catalytic and atom-efficient reactions. In parallel, Green Analytical Chemistry aims to develop analytical methods that require fewer chemicals, consume less energy, generate minimal waste, and maintain high standards of accuracy, precision, and reliability. Modern techniques such as microextraction, miniaturized analytical systems, green chromatography, and spectroscopic methods contribute significantly to environmentally responsible pharmaceutical analysis. The integration of these approaches enhances process efficiency, reduces operational costs, improves laboratory and worker safety, and supports compliance with environmental regulations while maintaining product quality. Furthermore, adopting sustainable practices aligns the pharmaceutical sector with global sustainability goals and encourages innovation in drug development and quality assurance. Despite challenges such as method validation, implementation costs, and technological adaptation, continuous advancements in green technologies are accelerating their industrial application. This poster highlights the principles, applications, benefits, challenges, and future prospects of Green Chemistry and Green Analytical Chemistry, emphasizing their combined role in achieving environmentally sustainable pharmaceutical manufacturing and analysis. Their widespread adoption represents a crucial step toward producing safer medicines while protecting human health and preserving the environment for future generations.